2020
DOI: 10.4269/ajtmh.20-0597
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Pulmonary Embolism in Returning Travelers with Hypoxemic Pneumonia due to COVID-19 in Reunion Island

Abstract: . The aim of this study was to evaluate the occurrence of pulmonary embolism in returning travelers with hypoxemic pneumonia due to COVID-19. All returning travelers to Reunion Island with hypoxemic pneumonia due to COVID-19 underwent computed tomography pulmonary angiography (CTPA) and were included in the cohort. Thirty-five patients were returning travelers with hypoxemic pneumonia due to COVID-19 and had recently returned from one of the countries most affected by the COVID-19 outbreak (mainly f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 8 publications
(12 reference statements)
0
17
0
Order By: Relevance
“…Therefore, the 66 remaining studies (including 43 studies reporting on ICU patients and 43 studies reporting on non‐ICU hospitalized patients) were included in quantitative data synthesis. 6,16‐81 …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the 66 remaining studies (including 43 studies reporting on ICU patients and 43 studies reporting on non‐ICU hospitalized patients) were included in quantitative data synthesis. 6,16‐81 …”
Section: Resultsmentioning
confidence: 99%
“…The cohort studies included 839 COVID‐19 patients in total, of which 186 developed different types of thrombotic events during the course of infection. 7 , 8 , 9 , 10 , 11 , 12 , 13 …”
Section: Resultsmentioning
confidence: 99%
“…Table 1 summarizes the types of thrombosis reported by the seven studies which included deep vein thrombosis (DVT), 7 , 8 , 9 , 10 , 11 , 12 pulmonary embolism (PE), 10 , 11 , 13 thrombosis in the aortic arch 11 and cerebral thrombosis. 12 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ventura-Díaz et al 20 Espallargas et al 25 Mueller-Peltzer et al 26 Ramadan et al 27 Mouhat et al 30 Alonso-Fernández et al 32 Monfardini et al 39 Freund et al 40 Chen et al 41 Whyte et al 43 Fauvel et al 45 Larsen et al 48 Bavaro et al 51 Mazzaccaro et al 53 Gervaise et al 54 Poyiadji et al 60 Bompard et al 62 BDL Overall (I 2 = 94.8%) patients with severe COVID-19. 68 It has been suggested that SARS-Cov-2 in severe forms of the disease induces an excessive inflammatory state via cytokine storm combined with endothelial injury and pulmonary vascular microthrombosis, which could considerably increase the risk for VTE, mainly PE.…”
Section: Table 1 (Continued)mentioning
confidence: 99%